The metabolic responses induced by acute dexamethasone predict glucose tolerance and insulin secretion over 10 years in relatives of type 2 diabetic subjects. Issue 6 (6th September 2013) - Durck, Tina Trier; Henriksen, Jan Erik; Egede, Mette Brogaard; Levin, Klaus; Rantzau, Christian; Ward, Glenn; Beck‐Nielsen, Henning; Alford, Frank P.
Abstract: Background: This study aimed to compare the metabolic and insulin secretory responses to dexamethasone with the metabolic responses observed at 10 years in normoglycaemic relatives of type 2 diabetic and healthy control subjects. Methods: Twenty relatives and 20 matched control subjects were studied twice at 0 year (pre‐ and post‐dexamethasone) and at 10 years, employing a 75‐g oral glucose tolerance test (OGTT), with serial measurements of glucose and insulin, for determination of glucose tolerance and calculations of acute insulin release (Δ I 30 /Δ G 30 ; insulinogenic index) and insulin sensitivity (SIHOMA ). Results: Following dexamethasone, the relatives group developed varying degrees of glucose intolerance, associated with reduced insulin sensitivity and insulinogenic index. By 10 years, fasting glucose and 2‐h OGTT glucose were raised in the relatives group, especially in the relatives most metabolically affected by dexamethasone, including a reduced insulinogenic index. Multiple regression analysis of the data in relatives demonstrated that the 2‐h OGTT glucose and fasting glucose values at 10 years depended on the 0‐year post‐dexamethasone 2‐h OGTT glucose, post‐dexamethasone fasting glucose and post‐dexamethasone insulin sensitivity, r 2 adj  = 56% ( p  < 0.001) and r 2 adj  = 60% ( p  < 0.0001), respectively. No pre‐dexamethasone metabolic or insulin secretory responses entered these models. Conclusions: In relatives, fasting and 2‐h OGTT glucose concentrations and β‐cell responses to acute dexamethasone‐induced insulin resistance are similar to those observed at 10 years, especially in relatives who develop the most disturbed dexamethasone‐induced glucose intolerance and impaired acute insulin secretion. The combined 0‐year, post‐dexamethasone fasting and 2‐h OGTT glucose concentrations and insulin resistance, measured as SIHOMA, are the best predictors in relatives of future dysglycaemia. Copyright © 2013 John Wiley & Sons, Ltd.